Analisis Kelayakan Usaha Industri Kecil Kerupuk Puli Tahu Di Desa Tlasih Kecamatan Tulangan Kabupaten Sidoarjo - Merlin Agustin; Muhammad Yasin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to analyze the feasibility of a small tofu cracker industry business in Tlasih Village, Tulangan District, Sidoarjo Regency. This type of research is descriptive research. The data analysis method used in this study is to use the formula for analysis of production costs, income and profits. Meanwhile, to analyze business feasibility, the formula used is Return On Investment (ROI) and Revenue Cost Ratio (R/C). The results of this study indicate that the average total cost of the 6 Puli Tahu cracker business owners is Rp. 41.565.810/month. The average income earned is Rp. 47.800.000/month with an average profit received of Rp. 6.234.819/month. Based on the results of a business feasibility analysis using the Return On Investment (ROI) formula which has an average value of 5,7% and Revenue Cost Ratio (R/C) which has an average value of 1,26. So it can be concluded that the small tofu cracker industry in Tlasih Village, Tulangan District, Sidoarjo Regency is feasible to cultivate.